La importancia de la educación sexual en el desarrollo socioemocional de los estudiantes del séptimo año de la Unidad Educativa "José Mejía Lequerica" en la parroquia de Machachi, cantón Mejía , provincia de Pichincha en el año lectivo 2016-2017 - Guerrero Guerrero, Daisy Maribel (2017)
This research is based on the importance to talk about Sexual Education to children and teenagers, in order to determine which are the cuases to hide this relevant information during the social emotional development from students of Unidad Educativa Jose Mejia Lequerica, that is located in Machachi, Mejia city in the Pichincha province , during 2016 and 2017 scholar year. This school is managed by 5 authorities and It has 65 teachers: 13 are men and 52 are women. Also It has 1476 students, Who are divided into the different years of Basic Education; 609 are boys and 865 are girls. The methodology, we have used during this research is: bibliographical, descriptive and scientific, that help us to transmit the true information about the topic and take advantage about these details, to imporve the learning skills that le tus to produce this research. In addition, we use the poll as a technique, this one give us the following conclusión: Sexual Education must be considered as a relevant aspect during the learning process and students’ emotional development due to: Parents, teachers and authorities don’t take into account this topic in their real dimension. So that, it’s important that we include this topic in the Educational Curriculum. So we can suggest that, Educative Community and Education District should organize Sexual Education talks, and they have to follow and evaluate these ones in order to identify the advantages and disadvantages and how students are improving their social emotional development, to avoid early sexual relationships, early pregnancies, abortions, rapes and other social problems. Finally, we have to take in to account that Sexual Education must be tough during the first years of the Basic Education using the correct didactic material in order for students to get the right information about the topic.